JENIS MODEL DAN METODE PEMBELAJARAN YANG DIGUNAKAN PADA TEMATIK 4 DI KELAS 3 SD PLUS 3 AL-MUHAJIRIN - Muharam, Agus; Nursyahbani, Andini; Firdaus, Dzulfa Nur; Farhanah, Reina; Mustikaati, Wina (JURNAL SINEKTIK, 2023)
Learning models and methods are very important components in the learning process. The existence of learning models and methods can help educators or teachers in conveying existing material. Learning models and methods vary widely and have their own specifications. The models and learning methods used in learning are not only one of them using role playing models, and team work. While the learning methods commonly used include lectures, discussions, and questions and answers. This study aims to find out the effectiveness of the 3rd grade thematic 4th grade learning models and methods with the theme 'obligations and my rights' at SD Plus 3 Al-Muhajirin. This study used Classroom Action Research (PTK) to obtain data by means of observations regarding learning models and methods in grade 3 elementary school. The results of this study serve as suggestions for educators in using models and methods of teaching and learning of the material. With the existence of learning models and methods, learning can take place in a fun and systematic way.